Surface geology and morphologic effects on seismic site response: The study case of Lampedusa, Italy. (April 2017) - Panzera, F.; Lombardo, G.; Sicali, S.; D'Amico, S.
Abstract: A joint Italo-Maltese research project (Costituzione di un Sistema Integrato di Protezione Civile Transfrontaliero Italo-Maltese, SIMIT) was financially supported by the European community with the aim to produce hazard maps in the area between the south-eastern Sicilian coast and the Sicily Channel including the islands of Lampedusa and Malta. In the frame of this project, the present study investigates the characteristics of the local seismic response in Lampedusa, a carbonate shelf belonging to the foreland domain at the northern edge of the African plate. Ninety-two ambient noise recordings were collected and processed through spectral ratio techniques. Polarization of the horizontal component of motion was also investigated in order to set into evidence possible directional effects. Results point out that in the central part of the island, where the most ancient and rigid terrains outcrop most of the spectral ratio plots show no particular site effects. On the other hand, nearby morphologic escarpments and fault lines, pronounced spectral ratio peaks in the frequency range 2.0–5.0 Hz are observed. These peaks, as highlighted by polarization analysis, are clearly directional with the largest amplification occurring with high angle (60°–90°) to the structures strike. Moreover, in sites located close to recent and soft deposits outcrops other significant seismic site effects at frequency higher than 5.0 Hz are identified. We can however assert that, rather than the surface lithology, the presence of cliff areas and tectonic structures strongly influence the local amplification of the ground motion and the occurrence of directional effects. Highlights: Ambient noise measurements in Lampedusa island. Data collected through a three component portable station. Data analyzed through spectral ratio techniques and polarization analysis. Obtained results were interpreted in function of outcropping lithology and morpho-structural features.